PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. DWINDO BERLIAN SAMJAYA KOTA TANGERANG SELATAN - Patriasih Andini; Ahmad Nazir (Journal of Research and Publication Innovation, 2024)
This research aims to determine the influence of work discipline and work environment on employee performance at PT. Dwindo Berlian Samjaya, South Tangerang City, both partially and simultaneously. This research method uses a quantitative method with an associative method, data collection used is a questionnaire and analyzed using SPSS 29 with a sample size of 57 respondents. The data analysis techniques used are instrument tests, classical assumption tests, simple linear regression tests, multiple linear regression tests, correlation coefficients, determination, partial hypothesis tests and simultaneous hypotheses to test and prove research hypotheses. The results obtained in the research were based on the t test on the Work Discipline variable tcount 3.055 > ttable 1.674 with a significance level of 0.000 < 0.05, meaning that Work Discipline (X1) partially and significantly influences Employee Performance (Y) and the Work Environment variable (X2) tcount is 2.064 and ttable is 1.674 with a significance level of 0.000 <0.05, meaning that the Work Environment (X2) partially and significantly influences employee performance (Y). Meanwhile, based on the results of the F test, it was found that the Fcount value was 58.824 > Ftable 3.168 with a significance level of 0.000 < 0.05, so it can be concluded that Work Discipline (X1) and Work Environment (X2) simultaneously and significantly influence Employee Performance (Y) at PT . Dwindo Berlian Samajaya South Tangerang City. With a coefficient of determination value of 68.5%.